circRNA circMED27 acts as a prognostic factor and mediator to promote lenvatinib resistance of hepatocellular carcinoma - Pengfei Zhang; Haixiang Sun; Peihao Wen; Yilin Wang; Yuehong Cui; Jing Wu (Elsevier, 2022)
Circular RNAs (circRNAs) have been proven to play key roles in the development and progression of various types of cancers. However, there were no reported studies on the roles of circRNA mediator complex subunit 27 (circMED27) in tumors including hepatocellular carcinoma (HCC). In this study, we found that circMED27 was significantly increased in HCC serum and that higher levels of circMED27 were correlated with bad clinical characteristics and poor prognoses of patients with HCC. Furthermore, upregulated circMED27 promoted HCC resistance to lenvatinib. Our mechanistic investigations revealed that circMED27 functions as a competing endogenous RNA (ceRNA) for miR-655-3p to upregulate ubiquitin-specific peptidase 28 (USP28) expression. Thus, we are led to conclude that circMED27 acts as a potential therapeutic target for HCC patients receiving lenvatinib therapy and may represent a promising molecular biomarker for forecasting lenvatinib-resistant HCC.